Changes in the kinetic properties of the a9a10 hair cell nicotinic receptor increase the level of olivocochlear inhibition in auditory synapses - Wedemeyer, Carolina (2016)
Medial olivocochlear (MOC) fibers innervate the cochlear outer (OHCs) hair cells and also transiently during development, the inner hair cells (IHCs). The MOC-hair cell synapse is cholinergic, inhibitory and is mediated by a9a10 nicotinic receptors (nAChR). In mice bearing a point mutation in the a9 nAChR subunit (Kin), in-vivo cochlear efferent-mediated inhibition is dramatically lengthened and enhanced (Taranda 2009). We now investigated whether there are changes in the short-term plasticity properties (STP) of MOC-hair cells synapses that could account for this enhanced efferent suppression. Evoked synaptic currents were recorded in IHCs and OHCs of isolated mouse organs of Corti. MOC-OHC synapses from Kin mice significantly facilitated upon 20 and 40 Hz stimulation (p2/p1- 20Hz= 2.6; p2/p1- 40Hz= 3.2; n=4-8). The probability of release increased during the trains, whereas the size of the events remained stable suggesting a presynaptic origin. Moreover, stimulation of MOC fibers at 80 Hz for 10 s resulted in postsynaptic responses of longer duration and slower onset times in both OHCs and IHCs from Kin mice (n=8-16). In accordance, preliminary experiments show that efferent inhibition of calcium action potentials is more potent in IHCs from kin mice. We conclude that the alteration in the STP patterns of MOC-hair cell synapses caused by the mutation could contribute to the observed changes in the dynamics of in-vivo cochlear efferent inhibition.